Optimizing the aluminum supply chain network subject to the uncertainty of carbon emissions trading market - Guo, Ying; Zhou, Wenji; Ren, Hongtao; Yu, Yadong; Xu, Lei; Fuss, Maryegli (Resources policy, 2023)
Aluminum production is characterized by high electricity consumption; hence its decarbonization hinges on upstream low-carbon electricity generation. As a result, the supply chain of aluminum product manufacturing can be strongly affected by the uncertainty of carbon emissions price via electricity generation. This paper investigates these impacts on the strategic design and the tactic operations of the aluminum supply chain by constructing a stochastic mixed-integer linear programming (SMILP) model, in which carbon price uncertainty and demand uncertainty are both accounted for. The supply chain case in the study covers a full process from upstream power generation to end-use consumption. A variety of stochastic carbon price scenarios are designed and assessed. Sensitivity analysis with respect to demand fluctuation is also performed. The results show that carbon price uncertainty significantly affects the configuration of the whole system. The main driving forces are the supplier selection and configuration alteration triggered by the carbon price variation, whereas other metrics such as carbon emissions costs and the responses to demand fluctuations display complicated patterns of change. This study provides a useful analytical framework that can be applied to the planning problem for other industries facing the same challenge. •An aluminum supply chain model accounting for carbon price uncertainty is developed.•Multiple power supply technologies with different emission patterns are incorporated.•Emissions reduction is determined by low-carbon energy system.•Demand uncertainty poses mixed effects on costs and emissions of the supply chain.